Signal Peptide Features Determining the Substrate Specificities of Targeting and Translocation Components in Human ER Protein Import - Lang, Sven; Nguyen, Duy; Bhadra, Pratiti; Jung, Martin; Helms, Volkhard; Zimmermann, Richard (Frontiers in Physiology, 2022)
In human cells, approximately 30% of all polypeptides enter the secretory pathway at the level of the endoplasmic reticulum (ER). This process involves cleavable amino-terminal signal peptides (SPs) or transmembrane helices (TMHs), which serve as targeting determinants, at the level of the precursor polypeptides and a multitude of cytosolic and ER proteins, which facilitate their ER import. Alone or in combination SPs and TMHs guarantee the initial ER targeting as well as the subsequent membrane integration or translocation. Cytosolic SRP and its receptor in the ER membrane mediate cotranslational targeting of most nascent precursor polypeptide chains to the polypeptide-conducting Sec61 complex in the ER membrane. Alternatively, fully-synthesized precursor polypeptides or certain nascent precursor polypeptides are targeted to the ER membrane by either the PEX-, SND-, or TRC-pathway. Although these targeting pathways may have overlapping functions, the question arises how relevant this is under cellular conditions and which features of SPs and precursor polypeptides determine preference for a certain pathway. Irrespective of their targeting pathway(s), most precursor polypeptides are integrated into or translocated across the ER membrane via the Sec61 channel. For some precursor polypeptides specific Sec61 interaction partners have to support the gating of the channel to the open state, again raising the question why and when this is the case. Recent progress shed light on the client spectrum and specificities of some auxiliary components, including the Sec62/Sec63 complex, TRAM1 protein, and TRAP complex. To address the question which precursors use a certain pathway or component in intact human cells, i.e. under conditions of faster translation rates and cellular crowding, in the presence of competing precursors, different targeting organelles, and relevant stoichiometries of the involved components, we combined siRNA-mediated depletion of single targeting or transport components in HeLa cells with label-free quantitative proteomics and differential protein abundance analysis. Here, we present a summary of the experimental approach as well as the resulting differential protein abundance analyses and discuss their mechanistic implications in light of the available structural data.